The Use and Usefulness of Big Data in Finance: Evidence from Financial Analysts - Chi, Feng; Hwang, Byoung-Hyoun; Zheng, Yaping (Management Science, 2025)
Alternative data have become a new source of information for investors. This paper examines how this development is reshaping the role of sell-side analysts. Employing textual analysis of analysts’ written reports, we show that analysts themselves have begun to adopt alternative data in their analyses. Furthermore, we find that when analysts report drawing from alternative data they generate more accurate earnings forecasts, and their brokerages subsequently receive higher amounts in trading commissions from investors, suggesting that investors value the adoption of alternative data by analysts. This paper was accepted by Kay Gieseke, finance. Funding: This research is supported by NTU-Singapore under its startup grant program. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.02659 .